Payment woes among Malaysian contractors - Che Munaaim, Muhammad Ehsan (2006)
Payment problems have prompted several developed countries to introduce construction-specific statutory security of payment acts typically known as construction contracts act to eliminate poor payment practices and smoothen the contractors’ cash flow. Malaysia too cannot pretend not to have these problems despite adequate mechanisms provided in many standard forms of construction contract. This paper presents findings of a study conducted amongst Malaysian contractors with the aims to determine the seriousness of late and non-payment problems, to identify the main causes and effects of late and non-payment and to identify remedies for securing payment debt as already been embedded in the construction contracts acts in other developed countries. It can be concluded that many local contractors have experienced late and non-payment problems in the Malaysian construction industry and the situation is far worse when it comes to government clients. This problem actually involves enormous amounts of money and leads to other problems that could affect the performance and image of the construction industry. The study via theoretical investigation and research survey found that the late and non-payment problems are contributed by inter alia: local culture/attitude, disagreement on the valuation of work done and paymaster's poor financial management. The study shows that late and non-payment can create cash flow problems, stress and undue financial hardship on the contractors. Amongst the most appropriate remedies to overcome or mitigate the problem of late and non-payment faced by local contractors include: a right to a speedy dispute resolution mechanism e.g. adjudication, a right to suspend work and a right to regular periodic payment. It is perhaps timely for Malaysia to introduce its own statute on the Payment and Adjudication Act.